A 6-week randomized-controlled field study: effect of isokinetic eccentric resistance training on strength, flexibility and muscle structure of the shoulder external rotators in male junior handball players - Vetter, Sebastian; Witt, Maren; Hepp, Pierre; Schleichardt, Axel; Schleifenbaum, Stefan; Roth, Christian; Denecke, Timm; Henkelmann, Jeanette; Köhler, Hans-Peter (Frontiers in Physiology, 2024)
Background: Team handball involves a tremendous amount of shoulder motion with high forces during repeated extended external range of motion. This causes shoulder complaints and overuse injuries. While eccentric training for the lower extremity shows preventive effects by improving strength, range of motion and fascicle length, there is a research gap for the shoulder joint and for advanced tissue characterization using diffusion tensor imaging.Objectives: To investigate the effects of six-week eccentric isokinetic resistance training on the strength, flexibility, and fiber architecture characteristics of the external rotators compared to an active control group in junior handball players.Methods: 15 subjects were randomly assigned to the eccentric training group and 14 subjects to the active control group (conventional preventive training). Primary outcome measures were eccentric and concentric isokinetic strength of the external rotators, range of motion, and muscle fascicle length and fascicle volume.The intervention group, showed significant changes in eccentric strength (+15%). The supraspinatus and infraspinatus muscles showed significant increases in fascicle length (+13% and +8%), and in fractional anisotropy (+9% and +6%), which were significantly different from the control group.Eccentric isokinetic training has a significant effect on the function and macroscopic structure of the shoulder external rotators in male junior handball players. While strength parameters and muscle structure improved, range of motion did not change. This research helps understanding the physiology of muscle and the role of eccentric training on shoulder function and muscle structure. Furthermore, DTI was found to be a promising tool for advanced tissue characterization, and the invivo derived data can also serve as model input variables and as a possibility to extend existing exvivo muscle models. Future research is needed for functional and structural changes following more convenient eccentric field exercises in this context.